Educación financiera para los comerciantes de las tiendas de abarrotes de los mercados de la ciudad de Loja - Manchay Trujillo, Dayanna Alexandra (2024)
Financial education is a tool that allows for the proper management of economic capital, it is becoming a highly relevant need for society to have knowledge about the use of financial products and services, this research work aims to propose a financial education programme aimed at grocery shops in the markets of the city of Loja, where the need for financial literacy was determined through an initial assessment. The study follows a mixed approach, with an exploratory, descriptive, experimental and descriptive scope, the research methods used were: analytical method, deductive method, inductive method and synthetic method; it was supported by the evaluation instrument that assesses financial literacy based on the PISA programme, the participating population are the owners of the businesses, classified as grocery shops in the six markets of the city of Loja. The results obtained indicate that the traders of the grocery shops in the city of Loja are at level 3 in terms of financial knowledge, which is why a financial education programme was designed and implemented with the objective of training the traders in the most relevant topics in this area; this programme allowed the participants in this research to reach level 5 in terms of financial knowledge. It is concluded that the application of the financial education programme had a positive impact on the traders of the grocery shops in the markets of the city of Loja, who were able to obtain indispensable knowledge for the correct administration of their businesses.